Strigolactone Preserves Fresh-Cut Apple Quality during Shelf Life - Zunchun Liu; Xinyu Zhang; Shuhua Zhu; Dandan Huang (Agriculture, 2024)
Strigolactone (SL) is a signal factor that plays a vital role in plants. The application of SL for the storability of horticultural products has recently received attention. In this experiment, fresh-cut apples were treated with SL at diverse concentrations and stored at 4 °C for 10 days, and the changes in quality characteristics, antioxidant system, hydrogen sulfide metabolism, and nitric oxide metabolism were determined. Compared with other treatments, the results showed that SL treatment at 0.50 µmol L−1 had excellent effects on maintaining fruit surface color, weight, firmness, reduced respiration rate, soluble solids content, and electrolyte leakage. SL treatment increased antioxidant enzyme activities, reduced reactive oxygen species (ROS) accumulation, altered the nitric oxide synthase (NOS)-like pathway to promote endogenous NO production in the fruit, and facilitated the L-cysteine-catalyzed process to increase the endogenous hydrogen sulfide (H2S) content. In addition, SL treatment affected the mRNA transcription levels of several genes related to the antioxidant system, H2S metabolism, and NO synthesis, including MdSOD, MdCAT, MdPOD, and MdSAT. Taken together, the results indicated that 0.50 µmol L−1 SL treatment improves the endogenous synthesis of NO and H2S, enhances the antioxidative system, and maintains the quality of fresh-cut apples during their shelf life. Therefore, the present study opens up the possibility of using the exogenous application of strigolactone in the fresh-cut processing industry.